71.1k views
2 votes
- 4x + 3x = 2 solveeeeeee

User DomiSchenk
by
5.4k points

2 Answers

2 votes
-4x + 3x = -x
-x = 2
-x/-1 2/-1
x = -2
User Nitza
by
6.6k points
3 votes

The right answer is x = -2

Below is first step:

First we need to pull out like factors :

-x - 2 = -1 • (x + 2)

Then equation is the last part of step 1

Second step:

You need to solve a single variable equation :

2.1 Solve : -x-2 = 0

Finally add 2 to both sides of the equation :

-x = 2

Multiply both sides of the equation by (-1) : x = -2

User Fralau
by
5.4k points